Pomen očesne banke za transplantacijo roženice - Pfeifer, Vladimir (Zdravniški vestnik, 2004)
Background. The paper describes the importance of donor tissue quality, minimum criteria for donor acceptance and procedures for taking the cornea from donor As important as surgical quality for successfull grafting is tissuequality regarding viral, bacterial and fungal contamination. We have to take care about proper postoperative care to prevent graft rejection. Conclusions. By standardization of minimal criteria for donor acceptance and careful donor selection the Eye banks are providing minimal risk for transmission of infective disease through corneal transplantation.
Keywords: Cadaver; Corneal Transplantation; darovalci; Eye Banks; Kadaver; merila; Očesne banke; roženica; Roženica, presaditev; standardi; Tissue Donors; Tissue Preservation; Tkivo, shranjevanje; Tkivodajalci; transplantacija